E-CATALOGUE INKUBATOR BISNIS IBI DARMAJAYA - Sri Lestari; Apri Triansyah; Yulmaini - (IIB Darmajaya, 2013)
IBI Darmajaya is one of the universities in Lampung, which has the vision of becoming a college superior and competitive base in technology and business. IBI Darmajaya so consent to make it happen, it can be seen in the curriculum and in line with the real action in preparing young people who have the entrepreneurial spirit. Business incubator is a place for the development of entrepreneurship from all societies, students, lecture, and staff. Business Incubator has progressed; it can be seen from the various types of businesses and products that are marketed as well as the increasing number of visitors. Some of the products made by students and lecturer have been marketed in the Business Incubator and the many partners who have entrusted the product for marketing. This development is a positive signal in realizing the vision of IBI Darmajaya. Therefore, it is time that the market share is not only for internal Darmajaya but to the public so increasingly wide range of its market. In order to achieve this, it takes a phenomenal breakthrough for Business Incubator as a business center embryo in Darmajaya, namely there's the e-Catalogue. The purpose of this study was to develop and result a software e-Catalogue Business Incubator IBI Darmajaya. E-Catalogue Incubator Binsnis IBI Darmajaya provide information to users about the types of businesses and products that exist in the Business Incubator, as well as a media campaign to support the development of a Business Incubator.Keywords: e-Catalogue, Business Incubator.